1997
DOI: 10.1063/1.365280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extremely fine Y2BaCuO5 precipitates on the critical current density of melt-processed YBa2Cu3Ox

Abstract: Based on previously developed melt processing methods, Y2BaCuO5 (211) precipitates with various size were obtained in YBa2Cu3Ox (123). In particular, a wide distribution of 211 size from 100 Å to 10 μm has been found to exist in the matrix of 123, and strongly effected the critical current density, Jc. An enhancement of Jc was always found to be associated with the presence of extremely fine 211 precipitates. The flux pinning by these precipitates can be understood by considering the interaction of flux lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…211 additive. We reported above the efficiency of the addition in large amounts of Y211 particles (up to 40% by weight) to stoichiometric Y123 to decrease the particle size of the Y211 phase coming from the decomposition of the Y123 precursor [50][51][52].…”
Section: Use Of Additivesmentioning
confidence: 99%
“…211 additive. We reported above the efficiency of the addition in large amounts of Y211 particles (up to 40% by weight) to stoichiometric Y123 to decrease the particle size of the Y211 phase coming from the decomposition of the Y123 precursor [50][51][52].…”
Section: Use Of Additivesmentioning
confidence: 99%
“…While some studies with bulk materials showed improvement of flux pinning with 211 addition, 15,[17][18][19][20] other studies reported otherwise possibly because of large 211 particle size. 3, 15-20 and references therein); however, there has been no attempt thus far to incorporate 211 particles directly into the microstructure of 123 thin films.…”
Section: Introductionmentioning
confidence: 99%
“…3, 15-20 and references therein); however, there has been no attempt thus far to incorporate 211 particles directly into the microstructure of 123 thin films. [17][18][19][20]. 16 In fully processed bulk materials, the 211 particle size is usually submicrometer to micrometer and the area particle density is typically very low, <10 10 cm −2 , although a very few 10-100-nm size particles can exist with area particle density <10 10 cm −2 (Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the transport properties of HTSCs, several methods [4,7], such as inclusion of impurities [8,9], partial substitution and preparation at high pressures [10], were developed. In addition to these procedures, it is generally accepted that the most suitable procedure to increase the critical current in HTSCs is the creation of an optimum density of defects with adequate distribution within the material.…”
Section: Introductionmentioning
confidence: 99%